Long‐Term Changes in Soil Carbon Stocks in the Brazilian Cerrado Under Commercial Soybean. (10th February 2016) - Miranda, Eduardo; Carmo, Janaina; Couto, Eduardo; Camargo, Plínio
Abstract: The net effect of agriculture on soil carbon is not yet fully understood. While a number of studies on shallow profiles have been published, evidence suggests that carbon stock changes occur in deeper layers. In this study we analyzed the effect of agriculture in the Cerrado soil C looking at changes in seven different profile depths from 0 to 100 cm in a commercial grain farm. We also used isotopic techniques to distinguish between the original Cerrado C3 carbon and the C4 carbon derived from the grasses used in agriculture. At 0–5 cm depth C stocks significantly decreased with cultivation time. The C stock did not change significantly when it was calculated using the 0–10, 0–20, 0–30, 0–50 or 0–75 cm profile ( p  > 0·05) but increased with cultivation time when the profile considered was 0–100 cm ( p  < 0·05). A two‐source isotope model revealed that there was a significant increase in carbon derived from C4 grasses for all depths with cultivation time. Annual carbon sequestration rates for the upper 100 cm of soil were 1·1 Mg C ha −1 year −1 for total carbon and 0·8 Mg C4 C ha −1 year −1 for C4 carbon. The oldest area, with 23 years of cultivation, had a soil C stock increase compared to the native Cerrado soil of 17·6%. These findings suggest that commercial grain farms practices may increase soil C stock compared to native Cerrado soil, if a more complete soil profile down to 100 cm is used to assess C stocks. Copyright © 2015 John Wiley & Sons, Ltd.